2019
DOI: 10.3390/nu11112598
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of Anthropometric Indices to Identify the Risk of Metabolic Syndrome

Abstract: Despite several papers having been published on the association between adiposity and the risk of metabolic syndrome (MetS), it is still difficult to determine unambiguously which of the indices of nutritional status is the best to identify MetS. The aim of this study was to analyze the ability of six anthropometric indices to identify MetS in the Polish population. The highest odds ratios for the occurrence of MetS, according to International Diabetes Federation (IDF), were noted for the following indices: wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
63
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 46 publications
(60 reference statements)
8
63
4
2
Order By: Relevance
“…However, BRI is limited in predicting percentage of fat mass in elite athletes when compared with other commonly and readily available field methods such as bio‐impedance analysis or skinfold prediction models 63 . Several recent studies have shown that BRI could be used as an adipose indicator for determining the presence of eccentric left ventricular hypertrophy, 64 hyperuricaemia, 41,65 arterial stiffness, 66–69 CVD, 70,71 diabetes, 41,72–75 dyslipidaemia, 41,76–78 hypertension 41,79,80 and MetS 41–55 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, BRI is limited in predicting percentage of fat mass in elite athletes when compared with other commonly and readily available field methods such as bio‐impedance analysis or skinfold prediction models 63 . Several recent studies have shown that BRI could be used as an adipose indicator for determining the presence of eccentric left ventricular hypertrophy, 64 hyperuricaemia, 41,65 arterial stiffness, 66–69 CVD, 70,71 diabetes, 41,72–75 dyslipidaemia, 41,76–78 hypertension 41,79,80 and MetS 41–55 …”
Section: Discussionmentioning
confidence: 99%
“…BRI is a predictor of body fat percentage and visceral adiposity tissue, and its values range from 1 to 16 35 . Although studies have compared the prediction of MetS by BRI with traditional and novel anthropometric indices, 41–55 there is currently no meta‐analysis indicating whether BRI is a better predictor of MetS than BMI, WC, WHR, WHtR, ABSI or BAI. Therefore, this meta‐analysis aims to investigate whether BRI is superior to BMI WC, WHR, WHtR, ABSI or BAI in predicting MetS.…”
Section: Introductionmentioning
confidence: 99%
“…That BMI and direct measurements of BF% are not strongly correlated has been known for over two decades [25,26]. In the general population, CUN-BAE has shown stronger correlations with direct measures of BF% than other anthropometric measures such as BMI, WC, body adiposity index (BAI), or body shape index (ABSI) [12,17,[19][20][21]. CUN-BAE-based on BMI, sex, and age-has been shown to be an independent measure of BMI [16].…”
Section: Discussionmentioning
confidence: 99%
“…CUN-BAE shows a strong correlation with BF% measured by direct techniques in all adults, especially in women, but studies in older adults are limited [15,20,21]. Also, the relation and concordance between the CUN-BAE and traditional anthropometrics are not clear, especially the relation with BMI as a component within the equation.…”
Section: Introductionmentioning
confidence: 94%
“…The early identification of metabolic disorders allows for an early intervention and the prevention of serious consequences. Overweight and obesity indices, calculated based on anthropometric measurements, have found a wide application in the identification of metabolic disorders [13][14][15][16][17][18]. The most significant advantages of anthropometric indices include the following: non-invasiveness, low cost, standardized techniques and simplicity of measurements, and the possibility to apply them on a large scale.…”
Section: Introductionmentioning
confidence: 99%